Preventif Care Melalui Media E-Booklet “Cerdi” dan Video Dapat Meningkatkan Pengetahuan dan Sikap Orang Tua dalam Pencegahan Diabetes Melitus pada Anak - Nissa, Suviola Khairu; Dahrizal, Dahrizal; Wijaya, Andra Saferi (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of preventive care through “cerdi” e-booklet media and videos on parents' knowledge and attitudes in preventing diabetes mellitus in children. The research method used was a pre experimental One Group pretest posttest design. The results showed that preventive care through the media e-booklet “cerdi” and video obtained a p-value of 0.000. In conclusion, preventive care through “cerdi” e-booklet media and videos can improve parents' knowledge and attitudes in preventing diabetes mellitus in children. Keywords: E-Booklet, Parents, Prevention of Diabetes Mellitus in Children, Knowledge, Attitude, Video